A four-stage constructed wetland system for treating polluted water from an urban river - Jia, Haifeng; Sun, Zhaoxia; Li, Guanghe (Ecological engineering, 2014)
•A four-stage wetland system was constructed to improve the water quality and flow pattern of a heavily polluted urban river.•The constructed wetland system composed of four interlinked units: a rapid filter, a down-flow subsurface constructed wetland, an up-flow subsurface constructed wetland, and a surface flow constructed wetland.•Weekly samples were taken at nine locations along the flow path of the wetland system during May 2011 to June 2012.•Results show significant improvements in the water quality and flow pattern of the urban river by the offsite wetland treatment system.•The four-stage constructed could be employed widely for water quality improvement and aesthetics enhancement in urban areas, especially water towns as described in the present study. A four-stage wetland was constructed to improve the water quality and flow pattern of a heavily polluted river in Luzhi Town, a water town in the Taihu Lake region of China. The four-stage constructed wetland system is composed of four interlinked units: a rapid filter, a down-flow subsurface constructed wetland, an up-flow subsurface constructed wetland, and a surface flow constructed wetland. The concentrations of chemical oxygen demand (COD), nitrogen and phosphorus, along the flow path of the constructed wetland, were measured and the pollutant removal efficiencies were calculated. The average removal rate over the whole wetland system was around 60% for COD and total phosphorus (TP), and around 70% for total nitrogen (TN) and ammonia nitrogen (NH4+-N). The total annual reduction in COD, TN, NH4+-N, and TP by the whole system was about 3.16t/yr, 0.57t/yr, 0.13t/yr, and 0.03t/yr, respectively. Following treatment of river water via the four-stage constructed wetland system, significant improvements resulted in the water quality and flow pattern of the polluted river.